A Welfare Analysis on Introducing Multi-Mode Service in Korea - Lee, Su Il (JOURNAL OF MEDIA ECONOMICS, 2015)
To conduct a welfare analysis on the introduction of Multi-Mode Service (MMS) in Korea, the article estimates demand equations for pay TV services and calculates the conversion rates of pay TV subscribers to terrestrial TV due to the MMS. Then a welfare analysis is performed. The analysis shows that the net present value of the MMS is less than 0 regardless of various models and scenarios, indicating that the introduction of MMS is economically infeasible in Korea. However, it should be noted that these results critically depend on the assumption on the degree of screen quality degradation of HD free terrestrial channels which will be caused by the introduction of MMS.